A reconfiguração pelos professores da proposta curricular de educação infantil - Barricelli, Ermelinda (2007)
This research exams and compares differet versions of Educational Curriculums by analyzing the representations about children, teacher, the Conception of learning teaching and the contents in the following documents: 1) National Curricular Referencial to Childhood Education, 2) Curriculum-I Elaborated by two day care centers in partnership with São Paulo City Halll; And 3) transcription of the Teachers Development meetings which goal was to elaborate collectively, a New Curriculum that I am naming Curriculum II. This work discusses, MEC prescription, the Institutional prescription, and the self prefiguration that show the childhood education teacher s job, as discussed by Bronckart & Machado (2004), Machado & Bronckart (2005), Clot (2004), and Filliettaz (2004). This research is based in the Socio-Historical- Cultural Theory, as discussed by Vygotsky and his collaborators, as well as by researches that rediscussed and amplified it (Daniels, 1994, 2001, 2002; Cole & Scribner, 2003; Newman & Holzman, 2002; Bronckart, 1997/2003, 2006; Clot, 2004). The discussions are focused on questions of childhood development, as pointed by Vygotsky (1924/1999, 1926/2003; 1930/2003; 1932/2003;1934/2001); about curricular questions (Apple, 1992, 1995; Apple & Beane, 2001; Giroux & Simon, 1995; Bassedas, Huguet & Solé, 1999); Oliveira, 2001; Sacristàn, 2000a, 2000d), and to questions about educational work (Amigues, 2002, 2004; Machado, 2004; Clot, 2004; Saujat, 2004; Bronckart, 2006). The Critical Research of Collaboration and the Socio Discursive Interactionism compose the theoretical methodological framework of this dissertation. The Critical Research of Collaboration is based on a conception of research in which the participants of the research participate in all the atages, since the elaboration until the final results, which allows the creation of a space to every member in the research to seek for theoretical paradigmatic changes (Magalhães, 1994, 2002, 2004; Magalhães & Liberali, 2005). The Socio Discursive Interactionism, more than a interdisciplinary conception is a science of human, crediting to the language and to the ways of acting fundamental role in the human development (Bronckart, 1993/2003; 2006, and Bronckart & Machado, 2004) and it was used as theoretical basis and table of analysis. This research made possible the elaboration of new categories of analysis, as well as the innovation in data collecting, focusing on three levels of documents related to teacher s job. This study alsos howed how the representations configured in the prescribed material circle in the métier of the job (Saujat, 2004) and 6 Tc (the) sediment in later documents related to the first one. Finally, it showed how the Curriculum of Childhood Education has a gap concerning contents to be developed with the children